Concept and marketing strategy for a new Starbucks brand product - Kadesnikova, Mariia; Bedřichová, Petra; Gburíková, Alžbeta; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
In the modern world, to maintain competitiveness, companies are forced to constantly introduce innovations to the market, including creating new products. The main goal of this thesis is to create a concept for a new Starbucks product and a marketing strategy for its eventual release. The author uses various methodologies, including literature research, analysis, observation, and a quantitative questionnaire. Based on literature research, the theoretical part covers the basic definition of marketing, including international marketing, new product development process, and marketing strategy theory. In the practical part, the thesis provides an overview of the Starbucks company and brand and delves into the author's observation - personal experiences working with the company. The primary focus lies in formulating and testing the idea of a new product, specifically a line of coffee drinks named "Taste of the Place," tailored to reflect local cultural differences and coffee traditions. The concept's viability is evaluated by conducting theory-based analysis and market research. They showed that the concept is unique and can help stand out from the competition. Then, to test the concept, the author conducted a quantitative questionnaire among Starbucks visitors, including regular customers, residents of the Czech Republic, and tourists from different countries. The survey results show promising interest among respondents. Subsequently, a comprehensive marketing strategy was developed, starting with a market analysis that confirmed the product's potential. Next, the product's target audience, positioning, and marketing goals were determined. Alongside the marketing strategy, a marketing mix was formulated.
Vedoucí práce: Petra Ivanega
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses